The Relationship Between the Left-Cradling Bias and Attachment to Parents and Partner. (7th May 2019) - Malatesta, Gianluca; Marzoli, Daniele; Piccioni, Chiara; Tommasi, Luca
Mothers usually cradle their infants to the left of their body midline, an asymmetry that seems to be a typically female lateral preference. This bias is deemed to be an evolutionary facilitator of communication between cradling and cradled individuals and is believed to be strongly related to hemispheric specialization for complex socio-affective behaviors. Thus, left cradling might facilitate affective interactions in females with typical brain organization, probably due to a right-hemisphere dominance for social attachment. In this study, we investigated cradling-side preferences in 288 young females as a function of their attachment styles to parents and partners. A left-cradling bias was more frequent in participants experiencing positive relationships with their mother and romantic partners. These findings indicate that the left-cradling bias may be associated with high-quality social attachment behaviors in females and, therefore, can be considered as a natural index of socio-emotional attunement between the cradling and cradled individuals.